(untitled) - Fazekas, Miroslav; Micietova, Maria; Sulgan, Marian (Doprava a spoje, 2012)
The article deals with the centers of freight transport and logistics warehouses in general. The problem of freight transport in urban centers cannot be restricted to problem of the distribution in the center of the city. Freight transport centers should be able to provide as much as possible logistic processes. Managing the warehouse storage organizes activities, strict control of stock, the determination of doses required for handling operations. Flexible organizational flows are provided by the electronic data collection, which also influences the policy-making and operating supplies in stock.